Lobbying legislatures - Morten Bennedsen; Sven E. Feldmann (Copenhagen Business School (CBS), Department of Economics, 2000)
We analyze informational lobbying in the context of multi-member legislatures. We show that a single decision maker and a decentralized majoritarian legis- lature provide widely di .erent incentives for interest groups to acquire and transmit policy relevant information. The paper also shows a di .erence in the opportunity to a .ect policy through lobbying between a parliamentary legislature and a legislature with low voting cohesion,such as the U.S.Congress.We show that the incentives to lobby a parliamentary legislature are much lower than to lobby Congress.The results provide a rationale for why lobby groups are more active n the U.S.Congress. The key institutional feature to explain the di .erent behavior of lobby groups is the vote of con .dence procedure,which creates voting cohesion in a parlia- mentary system across policy issues.We show that the .exibility of creating majorities in the Congress creates an incentive for interest groups to play an active role in the design of policy in the congressional system,while the voting cohesion in the parliamentary system dissuades interest group 's incentive to engage in information provision.
hdl:10398/7621
Keywords: H89; 330; Informational lobbying; legislatures; U.S. Congress